RESEARCH OF PHYSICAL AND CHEMICAL PROPERTIES OF GLYCOLS - Zaripov G.B.; Abdinazarova S.E. (Лучшие интеллектуальные исследования, 2024)
Annotation. Improvement of technical and economic indicators of gas field operation and reduction of previously listed negative factors can be achieved by obtaining a regenerated absorbent with a residual water content of no more than 0.5% when operating a desorption column with a bottom temperature value not approaching the thermal decomposition temperature used glycol. The paper discusses alternative ways to increase the efficiency of mass transfer processes of water molecules from the produced reservoir gas to the phase of glycol on the absorber plates and boiling water from the saturated volume of absorbent in its regeneration unit.